Transmission of memories about the dictatorship: reappropriation of the adult generation’s discourse by young people - Baeza Duffy, Patricia (Árboles y Rizomas, 2023)
This qualitative study is part of a larger research on the transmission of memories from the adult generation to the new generations, through different sources: family, friends, acquaintances, schools, museums, television programs, documentaries, songs and other cultural practices related to the last Chilean dictatorship and its projection in the present. This paper aims to analyze the ways in which young people appropriate and re-signify the discourse of others. The theoretical-methodological perspective adopted integrates the Appraisal framework and Critical Discourse Studies. The corpus consists of interviews conducted with six students whose ages range from fourteen to sixteen years old at the moment of being interviewed. Findings show ideological positionings of the young people themselves, whose discourses contain evaluations, inscribed or evoked, positive or delegitimizing about the dictatorship and its aftermath at present. The new generation reinterprets or resignifies these memories constructed by adults in order to integrate them into their own experience. In addition, the discourse of the interviewees show diverse processes of recontextualization and a predominance of strategies to transform the situation caused by the dictatorship and its consequences in the current Chilean society in which they are immersed.
Keywords: intergenerational transmission; memories; recontextualization; reapropriation; transformation